The food crisis of 2008: Impact assessment of IFPRI's communications strategy - Hovland, Ingeborg (International Food Policy Research Institute, 2009)
This paper aims to document IFPRI’s communications activities during the recent food crisis which peaked in mid-2008. IFPRI’s communications activities during the food crisis were somewhat unusual for the Institute. The communications campaign included IFPRI’s usual avenues, and built on IFPRI’s existing place in the global food policy system, but was unusual in its concerted coordination across all divisions of the Institute, the relatively low number of publications and unusually high engagement with the media, as well as a high number of face-to-face presentations and meetings. All in all the campaign, which arose in response to the policy window that opened up in early and mid-2008, was considered particularly effective, and IFPRI earned the position as one of the “thought leaders” during the crisis.